2003
DOI: 10.1128/aem.69.3.1482-1487.2003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Spatial and Genetic Distance in Agrobacterium spp. in 1 Cubic Centimeter of Soil

Abstract: The spatial and genetic unit of bacterial population structure is the clone. Surprisingly, very little is known about the spread of a clone (spatial distance between clonally related bacteria) and the relationship between spatial distance and genetic distance, especially at very short scale (microhabitat scale), where cell division takes place. Agrobacterium spp. Biovar 1 was chosen because it is a soil bacterial taxon easy to isolate. A total of 865 microsamples 500 m in diameter were sampled with spatial coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 33 publications
3
32
1
1
Order By: Relevance
“…Therefore, at the smallest scale sampled here, multiple clones co-occurred. Overlapping of clones at small spatial scales has been found for other soil microbes [25,58,69]. A recent study focusing on actinomycetes also revealed high diversity among isolates of closely related genera from a single soil sample [44].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, at the smallest scale sampled here, multiple clones co-occurred. Overlapping of clones at small spatial scales has been found for other soil microbes [25,58,69]. A recent study focusing on actinomycetes also revealed high diversity among isolates of closely related genera from a single soil sample [44].…”
Section: Discussionmentioning
confidence: 92%
“…To identify local factors that may influence the spatial distribution of diversity, including competitive interactions and resource availability, information on how phenotypes and genotypes are arrayed in space is crucial. There is a growing body of empirical studies examining the spatial distribution of genetic diversity in the soil at a range of spatial scales from micrometers to kilometers [3,8,20,25,48,56,69).…”
Section: Introductionmentioning
confidence: 99%
“…They vary orders of magnitude in size. Bacterial cells, colonies, and biofilms-measured in micrometers to centimeters (Vogel et al 2003, Grundmann 2004)-are consistently the smallest of the three. Litter fungi range from unicellular yeasts (tens of micrometers) to filamentous hyphal cells that occupy several square meters of the forest floor (Lodge andCantrell 1995, Redecker et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Analisis juga dapat mentarget hanya suatu klaster gen seperti ribotyping pada operon rrn (Khetawat et al, 1999), atau bahkan gen individual seperti ARDRA (Vogel et al, 2003) dan T-RFLP (Dunbar et al, 2001) pada gen penyandi 16S rRNA, intergenic spacer regions/ISR (Garcia-Martinez et al, 1999), serta elemen genetik mobile (Gordon et al, 1999;Papadopoulus et al, 1999).…”
Section: Definisi Spesies Prokaryotaunclassified